Peningkatan Daya Saing Produk Usaha Mikro Keripik Bakso Goreng Di Kota Bandung Melalui Strategi Packaging Inovatif dan Optimalisasi Promosi Media Sosial - Terra Saptina Maulani (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
The creative economy sector is one of the pillars of economic growth in Indonesia and creativity is the basis for economic development activities. Efforts to grow the economy after the COVID-19 pandemic are not easy and the adaptation efforts in the new normal era are to increase creativity for competitiveness. Bandung has many creative economy entrepreneurs, especially in the culinary sector and the contribution to local income is about 57%, its become the priority. sector. The favorite snacks of local people and tourists buy as a gift from Bandung is fried meatball chips. it's one of the top 10 gifts from Bandung. One of the micro business unit in the culinary sector that produces “modern” fried meatball chips is Hwaps.id. It has potential because the customer of this product is not only regional but it has been delivered several times outside Bandung and Java Island. The problem is packaging is very simple so it is less competitive due to the age of the product being less durable and lack of clear information on the label so there is a need for an innovative packaging strategy, and the ineffective use of social media because it is not managed properly so training is needed to optimize social media as a promotional tool.